Influences of halal product integrity and halal industry macro-environments on marketing program adaptation and export performance among Malaysian export firms - Hassan, Hazlinda (2013)
To successfully optimize the enormous opportunities in the global Halal market,exporting firms must be prepared to adapt their marketing strategies to reflect the unique circumstances of the market. Accordingly, the main purpose of the study is to explore the influence of product and macro-environmental factors specific to the Halal industry on marketing program adaptation and export performance. Using a mixed methods research approach, semi-structured interviews with 12 selected experts in the Halal industry were conducted initially to explore the specific dimensions of Halal product integrity and Halal industry macro-environments. Later, the questionnaires were distributed to 110 Malaysian Halal exporting firms. Based on the survey, the results of Partial Least Squares (PLS) analysis revealed that ethical integrity,Halal regulations and support, Halal values and attitudes, and Halal technological development were significantly and positively related to the decision to adapt the marketing program. Meanwhile, physical integrity and Halal economic indicators were not perceived as important in a firm’s decisions for export marketing adaptation. The study also found a partial role of marketing program adaptation strategy in mediating the influence of ethical integrity on export performance, and also the influence of Halal regulations and support on export performance. The results are useful to public export agencies and exporting firms in designing appropriate strategies to improve export performance of Halal products. The findings suggested that firms wishing to achieve superior export performance should assess carefully the diverse expectations of ethical integrity among product categories and market segments, understand various regulations concerning Halal products and trades, and be responsive toward government support. Firms should also be aware of the unique conditions of the Halal industry’s macro-environments in a country so as to perform the appropriate adaptation for each marketing program. The study has filled a gap in the literature by empirically establishing the influence of product and macro-environmental factors of the Halal industry on marketing program adaptation and export performance, and adding a single industry value to the existing body of knowledge. The study has also advanced the knowledge of the export marketing field by integrating Islamic marketing principles into the current research framework.